Pop mladina - Tomc, Gregor (Teorija in praksa, 2014)
The author discusses some key approaches to understanding youth in modern societies (generational identity, peer groups, communitas, moratorium) and differences in the social construction of youth in part-modern (fascism, Nazism, communism) and modern states (political democracies). He then discusses the difference between cultural studies of youth in Great Britain after the Second World War and research of youth in the context of socialism as well as in the context of political democracy in Slovenia. During socialism, the hegemonic approach to social science was class analysis and, as a result, youth was perceived as an ideological construct. There was no interest in research into youth lifestyles. The first research of youth subcultures was only carried out in the 1990s. In the concluding discussion, the author explains this research lag with the underdeveloped cultural industry, the smallness of the Slovenian cultural space and the conservatism of its cultural milieu.
Keywords: Cultural industries; Cultural studies; Great Britain; Kulturna industrija; Kulturne študije; Mladina; popularna kultura; Slovenia; Slovenija; Subculture; Subkultura; Velika Britanija; Youth